Benzyl Triethyl Amonium Chloride (BETAC) As Inhibitor Corrosion On Steel - Suyanto, Dr. Ir. M.Si. (2011)
Inhibition test on the iron corrosion using solution of benzyl triethyl amonium cloride (BETAC) was performed. The iron of plate was soaked on 0.5 M of sulfuric acid solution and added BETAC solution with concentrations 0.1; 0.25 and 0.5 M during 7, 14, 21 and 28 days, respectively. The highest of inhibition efficiency is 74.22% at day 7 th.